Functional impulsive differential equation of order α∈(1, 2) with nonlocal initial and integral boundary conditions. (31st August 2016) - Gupta, Vidushi; Dabas, Jaydev
Abstract : The main work is related to show the existence and uniqueness of solution for the fractional impulsive differential equation of order α ∈(1, 2) with an integral boundary condition and finite delay. Using the application of the Banach and Sadovaskii fixed‐point theorems, we obtain the main results. An example is presented at the end to verify the results of the paper. Copyright © 2016 John Wiley & Sons, Ltd.